PENDAMPINGAN WAWASAN GENDER DALAM DIALEKTIKA AL-QURAN DAN BUDAYA PATRIARKI PADA SISTEM WARIS 2:1 PERSPEKTIF HISTORIS HUMANISTIK DI MAHAD AL-QURAN UNIVERSITAS PTIQ JAKARTA - Nurbaiti Nurbaiti; Syamsuri Syamsuri; Aas Siti Sholichah; Abd. Rohim; Hamka Hasan; Jarudin Jarudin (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2023)
This study aims to analyze verses regarding the inheritance system stipulated in 2:1 between men and women. The underlying issue of this research is the interpretive polarization between feminism and androcentrism, often grounded in their respective ideologies. By conducting objective and in-depth analysis, this research is expected to address such interpretive polarization and open up space for a more holistic understanding of the messages of the Qur'an. This study employs a historical approach with the religious humanistic theory perspective of Muhammad Thalbi. The historical context encompasses cultural values and social conditions, both pre-revelation and post-revelation. The historical data is analyzed using two analytical models, descriptive and explanatory. The findings indicate that the pre-revelation period, particularly the era of Jahiliyyah, serves as a key element in clarifying the influence of time periods, social conditions, and historical events that shape the Qur'anic paradigm. The inheritance provisions for women in the Qur'an provide a concrete conceptual and normative basis for protecting, respecting, and empowering women in various aspects of life. Analysis using the historical humanistic approach in the inheritance provision of 2:1 between men and women demonstrates that the justice initiated by the Qur'an is distributive justice. This is because the policy in inheritance division cannot be separated from the obligation of men to provide dowry and sustenance for women in family life